Anti-Acanthamoeba synergistic effect of chlorhexidine and Garcinia mangostana extract or alpha-mangostin against Acanthamoeba triangularis trophozoite and cyst forms - Sangkanu, Suthinee; Mitsuwan, Watcharapong; Mahabusarakam, Wilawan; Jimoh, Tajudeen O.; Wilairatana, Polrat; Girol, Ana Paula [UNESP]; Verma, Ajoy K.; Pereira, Maria de Lourdes; Rahmatullah, Mohammed; Wiart, Christophe; Siyadatpanah, Abolghasem; Norouzi, Roghayeh; et al. (Nature Research, 2021)
Acanthamoeba spp. can cause amoebic keratitis (AK). Chlorhexidine is effective for AK treatment as monotherapy, but with a relative failure on drug bioavailability in the deep corneal stroma. The combination of chlorhexidine and propamidine isethionate is recommended in the current AK treatment. However, the effectiveness of treatment depends on the parasite and virulence strains. This study aims to determine the potential of Garcinia mangostana pericarp extract and alpha -mangostin against Acanthamoeba triangularis, as well as the combination with chlorhexidine in the treatment of Acanthamoeba infection. The minimal inhibitory concentrations (MICs) of the extract and alpha -mangostin were assessed in trophozoites with 0.25 and 0.5 mg/mL, for cysts with 4 and 1 mg/mL, respectively. The MIC of the extract and alpha -mangostin inhibited the growth of A. triangularis trophozoites and cysts for up to 72 h. The extract and alpha -mangostin combined with chlorhexidine demonstrated good synergism, resulting in a reduction of 1/4-1/16 of the MIC. The SEM results showed that Acanthamoeba cells treated with a single drug and its combination caused damage to the cell membrane and irregular cell shapes. A good combination displayed by the extract or alpha -mangostin and chlorhexidine, described for the first time. Therefore, this approach is promising as an alternative method for the management of Acanthamoeba infection in the future.